1989
DOI: 10.1093/oxfordjournals.jbchem.a122923
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the 27-kDa Gap Junction Protein by Protein Kinase C In Vitro and in Rat Hepatocytes

Abstract: We previously demonstrated that the 27-kDa major component protein in rat liver gap junctions was phosphorylated by protein kinase C in vitro (Takeda, A. et al. (1987) FEBS Lett. 210, 169-172). In this study, we examined this further and examined the phosphorylation of the 27-kDa gap junction protein in rat hepatocytes by metabolically labeling cells with [32P]orthophosphate and using a monoclonal antibody to immunoprecipitate the protein. The in vitro phosphorylation was inhibited by monoclonal antibodies rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Activation of either cAMP-dPK or PKC increases the state of phosphorylation of Cx32 (34,63,70,72) and at least the effect of cAMP-dPK is temporally correlated with an increased junctional conductance (g j ). Moreover, Chanson et al (71) reported that an increase in intracellular [cAMP] in a human colonic T84 cell line induces a rapid (<20 min) increase in intercellular gap junctional communication mediated by Cx32 gap junctions, that is directly related to an increase in fluid secretion.…”
Section: Effect Of Cx32 Phosphorylation On Intercellular Gap Junctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of either cAMP-dPK or PKC increases the state of phosphorylation of Cx32 (34,63,70,72) and at least the effect of cAMP-dPK is temporally correlated with an increased junctional conductance (g j ). Moreover, Chanson et al (71) reported that an increase in intracellular [cAMP] in a human colonic T84 cell line induces a rapid (<20 min) increase in intercellular gap junctional communication mediated by Cx32 gap junctions, that is directly related to an increase in fluid secretion.…”
Section: Effect Of Cx32 Phosphorylation On Intercellular Gap Junctionmentioning
confidence: 99%
“…cAMP increases the amount of metabolically labelled Cx32 in primary cell cultures of fetal hepatocytes (70), implying either an increased rate of synthesis or a reduced rate of degradation. The stoichiometry of phosphorylation of Cx32 in vitro is low; by PKC it approaches 1 mol/mol and by cAMP-dPK it is about 0.1 mol of P i /mol of protein (34,63,72). Nevertheless, the stoichiometry of phosphorylation in vivo and the cell compartment in which Cx32 phosphorylation occurs have not been determined.…”
Section: Effect Of Cx32 Phosphorylation On Intercellular Gap Junctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used experimental approaches to demonstrate that a particular Cx is a phosphoprotein include metabolic labeling of cultured cells with 32 P followed by immunoprecipitation and alkaline phosphatase treatment, phosphoamino acid analysis (Sáez et al 1986;Takeda et al, 1989;Musil et al, 1990;Crow et al, 1990;Sáez et al, 1990;Lau et al, 1992;Goldberg and Lau, 1993;Kurata and Lau, 1994;Doble et al, 1996;Warn-Cramer et al, 1996;Mikalsen et al, 1997;Cheng and Louis, 1999) or two-dimensional phosphopeptide mapping (Sáez et al, 1990;Kurata and Lau, 1994;Díez et al, 1995;Loo et al, 1995;WarnCramer et al, 1996;Berthoud et al, 1997;Díez et al, 1998;Kanemitsu et al, 1998) in vitro phosphorylation assays using fusion proteins or synthetic peptides containing the putative phosphorylation site(s) and purified protein kinases (Sáez et al, 1990;Loo et al, 1995;WarnCramer et al, 1996;Berthoud et al, 1997;Kanemitsu et al, 1998;Shah et al, 2002;O'Brien et al, 2004;Ouyang et al, 2005;Yogo et al, 2006;Alev et al, 2008;Morel et al, 2010); treatment of cultured cells with specific protein kinase or phosphoprotein phosphatase activators or inhibitors to alter 32 P incorporation or the immunoblot pattern of connexins (Lau et al, 1992;Husøy et al, 1993;Guan et al, 1996;Berthoud et al, 1997;…”
Section: Methods Used To Demonstrate That Connexins Are Phosphoproteinsmentioning
confidence: 99%
“…The first reports that demonstrated a particular Cx to be a phosphoprotein using metabolic labeling with 32 P showed phosphorylation of Cx32 in hepatocytes (treated with phorbol esters, OAG, forskolin or cAMP analogs)( (Sáez et a., 1986;Takeda et al, 1989;Sáez et al, 1990) and phosphorylation of Cx43 in uninfected and Rous sarcoma virus (RSV)-transformed fibroblasts (Crow et al, 1990). Phosphoamino acid analysis indicated that hepatocyte Cx32 and Cx43 in uninfected fibroblasts were phosphorylated on seryl residues (Takeda et al, 1989;Crow et al, 1990;Sáez et al, 1990), but Cx43 was also phosphorylated in tyrosyl residues in RSV-transformed fibroblasts (Crow et al, 1990).…”
mentioning
confidence: 99%